2005
DOI: 10.1063/1.1978985
|View full text |Cite
|
Sign up to set email alerts
|

Structure and property investigation of a Bi-based perovskite solid solution: (1−x)Bi(Ni1∕2Ti1∕2)O3–xPbTiO3

Abstract: Extending the investigations on Bi-based perovskite solid solutions for high-temperature piezoelectric ceramics, this paper considers the binary solid-solution system (1−x)Bi(Ni1∕2Ti1∕2)O3–xPbTiO3 [(1−x)BNT–xPT] for 0.39⩽x⩽1.00. High-density polycrystalline ceramics were fabricated using conventional solid-state processing methods. These ceramics are then taken for structural and electrical properties and differential scanning calorimetry measurements. A morphotropic phase boundary (MPB) was found at the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
118
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 15 publications
8
118
0
Order By: Relevance
“…The crystal and magnetic structure of the stabilized system may be different from the initial components after the formation of solid solution. Following this route, phase pure perovskite form of BNT has been stabilized at ambient pressure by forming its solid solution with other ceramics such as PbTiO 3 [24], Pb (1-x) Sr x TiO 3 [25], BaTiO 3 , SrTiO 3 etc. The structure of BNT is double perovskite with orthorhombic space group Pn2 1 a obtained by the repetition of monoclinic unit cells [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal and magnetic structure of the stabilized system may be different from the initial components after the formation of solid solution. Following this route, phase pure perovskite form of BNT has been stabilized at ambient pressure by forming its solid solution with other ceramics such as PbTiO 3 [24], Pb (1-x) Sr x TiO 3 [25], BaTiO 3 , SrTiO 3 etc. The structure of BNT is double perovskite with orthorhombic space group Pn2 1 a obtained by the repetition of monoclinic unit cells [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…12͒ and Bi͑Mg 1/2 Ti 1/2 ͒O 3 -PbTiO 3 , 13 all known BiMeO 3 -PbTiO 3 -based systems have low or inferior piezoelectric properties at their MPB. As Bi͑Ni 1/2 Ti 1/2 ͒O 3 -PbTiO 3 suffers from high conductivity and dielectric losses, 12 we chose Bi͑Mg 1/2 Ti 1/2 ͒O 3 -PbTiO 3 for our current study.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The operating temperature of piezoelectric ceramics is generally limited to one-half of the Curie point ͑T C ͒ due to loss of polarization, typically at temperatures lower than 200°C ͓e.g., 150°C for the conventional piezoelectric materials based on the Pb͑Zr 1−x Ti x ͒O 3 ͑PZT͔͒ with a Curie temperature, T C = 386°C. 4 After excellent piezoelectric properties for ͑1 − x͒BiScO 3 -xPbTiO 3 ͑BS-PT͒ near the morphotropic phase boundary ͑MPB͒ ͑x = 0.64͒ were reported ͑piezoelectric coefficient, d 33 = 460 pC/ N, planar coupling coefficient, k p = 0.56, and T C = 450°C͒ recently, 5,6 the discovery of several promising high temperature piezoelectric materials with high performance followed in the general BiMeO 3 -PbTiO 3 system, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] where Me can be a single cation of valency +3 ͑e.g., Sc 3+ and Fe 3+ ͒ or a mixture of cations with an average valence of +3 ͑e.g., Mg 1/2 Ti 1/2 and Ni 2/3 Nb 1/3 ͒. It has been proposed that the Bi substitution plays an unusual role of considerable enhancement of both Curie temperature ͑T C ͒ and tetragonality ͑c / a͒, which results from a strong coupling between Pb/Bi cations and B-site cations of strong ferroelectric activity, such as Ti, Zn, and Fe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 It was expected that the Bi(Me)O 3 -PbTiO 3 compositions with higher T c > 300 C will shed light on the potentiality of achieving high temperature stability. [21][22][23][24][25][26] However, except BiScO 3 -PbTiO 3 (BS-PT), 21 the piezoelectric coefficients of the reported Bi(Me)O 3 -PbTiO 3 based ceramics, such as BiFeO 3 -PbTiO 3 (BF-PT), 22 BiInO 3 -PbTiO 3 (BI-PT), 23 Bi(Ni 1/2 Ti 1/2 )O 3 -PbTiO 3 (BNT-PT), 24 Bi(Mg 1/2 Ti 1/2 )O 3 -PbTiO 3 (BMT-PT), 25,26 etc., were lower than 300 pC/N at their respective MPBs. Furthermore, it was reported that piezoelectric coefficients exhibited different degree of degradation in binary and ternary systems, not necessarily associated with their T c /T rt , though higher T c indicating broader usage temperature range.…”
mentioning
confidence: 99%